Surface defect detection / Muhammad Haziq Salman and Anas Zafirol Abdullah Halim - Salman, Muhammad Haziq; Abdullah Halim, Anas Zafirol (2023)
The study highlights the importance of prioritising consistency and quality in precast concrete construction using surface defect detection. Precast concrete offers numerous advantages in construction projects, with standardised components produced in a centralised plant using factory prefabrication. The aim of this research is to use surface defect detection to monitor the quality and consistency of precast concrete material. The objective of this study is to specifically focus on surface defect detection in order to enhance the consistency and quality of precast concrete components. By implementing a monitoring system that utilises advanced technologies, such as computer vision and image processing, defects in precast concrete elements can be detected and addressed at an early stage. This proactive approach mitigates the risk of compromised structural integrity, delays, and increased costs. The study emphasises the need for continuous monitoring throughout the production process to identify and rectify surface defects, including cracks, scratches, and irregularities. By integrating surface defect detection into the precast concrete manufacturing workflow, manufacturers can improve product quality, optimise production efficiency, and meet the highest standards of construction.